Genome Functional Analysis of the Psychrotrophic Lignin-Degrading Bacterium Arthrobacter sp. C2 and the Role of DyP in Catalyzing Lignin Degradation - Jiang, Cheng; Yan, Haohao; Shen, Xiaohui; Zhang, Yuting; Wang, Yue; Sun, Shanshan; Jiang, Hanyi; Zang, Hailian; Zhao, Xinyue; Hou, Ning; Li, Ziwei; Wang, Liwen; et al. (Frontiers in Microbiology, 2022)
In the cold regions of China, much of the lignin-rich corn straw accumulated due to the low temperature limiting. The application of psychrotrophic lignin-degrading bacteria should be an effective means of overcoming low-temperature limit of lignin degradation and promoting the utilization of corn straw. However, the lack of strain resources hinders the decomposition of lignin; furthermore, the metabolic mechanism of psychrotrophic lignin-degrading bacteria is unclear. Here, the whole genome of the psychrotrophic lignin-degrading bacterium Arthrobacter sp. C2, isolated in our previous work, was sequenced. Comparative genomics revealed that C2 contained unique genes related to lignin degradation and low-temperature adaptability. DyP may participate in lignin degradation and may be a cold-adapted enzyme. Moreover, DyP was proven to catalyze lignin Cα-Cβ bond cleavage. DyP gene deletion and complementation verified its ability to catalyze the first-step reaction of lignin degradation. Comparative transcriptome analysis revealed that the transcriptional expression of DyP gene was induced upregulation, and the genetic compensation mechanism endowed C2ΔDyP viability on lignin, which provided novel idea for explaination the survival strategy of the psychrotrophic mutant strain C2ΔdyP. This study improved our understanding of metabolic mechanism of psychrotrophic lignin-degrading bacteria and provided potential application options for energy-saving production using cold-adapted lignin-degrading enzymes.